2013
DOI: 10.3851/imp2442
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Trial of Intravenous Peramivir Compared with Oral Oseltamivir for the Treatment of Seasonal Influenza in Hospitalized Adults

Abstract: Treatment of acute seasonal influenza in hospitalized adults with either peramivir or oseltamivir resulted in generally similar clinical outcomes. Treatment with peramivir was generally safe and well tolerated and could be of benefit in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 31 publications
4
77
3
Order By: Relevance
“…The negativity rates were consistent, although somewhat lower than previously described for hospitalised patients (97-100% and 60-82%, respectively, on Day 4-5), which might be explained by the fewer LRTC cases (20-50%) in other cohorts [5][6][7]. Compared with our patients treated with oseltamivir, we found that the virological responses were generally similar [1,5,6,10]. Interestingly, when compared against the oseltamivir subgroup with LRTC, we observed a trend towards faster viral decline with peramivir.…”
Section: Discussionsupporting
confidence: 46%
See 3 more Smart Citations
“…The negativity rates were consistent, although somewhat lower than previously described for hospitalised patients (97-100% and 60-82%, respectively, on Day 4-5), which might be explained by the fewer LRTC cases (20-50%) in other cohorts [5][6][7]. Compared with our patients treated with oseltamivir, we found that the virological responses were generally similar [1,5,6,10]. Interestingly, when compared against the oseltamivir subgroup with LRTC, we observed a trend towards faster viral decline with peramivir.…”
Section: Discussionsupporting
confidence: 46%
“…There was a −2.0 log viral load reduction by Day 3 and −2.5 log by Day 5, and 94% and 44% achieved culture and RNA negativity, respectively, on Day 5. The negativity rates were consistent, although somewhat lower than previously described for hospitalised patients (97-100% and 60-82%, respectively, on Day 4-5), which might be explained by the fewer LRTC cases (20-50%) in other cohorts [5][6][7]. Compared with our patients treated with oseltamivir, we found that the virological responses were generally similar [1,5,6,10].…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…Ison et al26 conducted a multinational Phase II randomized, double-blind trial in seven countries to evaluate the efficacy and safety of intravenously administered peramivir compared to oral oseltamivir in 2007–2008, the prepandemic era. The 137 adult hospitalized patients with suspected acute seasonal influenza were randomized to 5-day treatments with intravenously administered peramivir (400 mg or 200 mg once daily) or oral oseltamivir (75 mg twice daily).…”
Section: Resultsmentioning
confidence: 99%